2009
DOI: 10.1007/s12132-009-9062-0
|View full text |Cite
|
Sign up to set email alerts
|

Inter-generational Occupational Mobility Amongst Blacks in the Mitchell’s Plain Magisterial District, Cape Town: Evidence from the Khayelitsha/Mitchell’s Plain Survey

Abstract: This study examines inter-generational occupational class mobility amongst blacks (Africans and coloureds) in the Mitchell's Plain Magisterial District in Cape Town, South Africa. The results of the Khayelitsha/Mitchell's Plain Survey conducted in 2000 serve as the main source of data. We show that middle-class occupational origins do not necessarily guarantee the transmission of advantage from one generation to the next. The findings revealed that there is a churning effect at work with respondents experienci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Our own and other work suggest that, over time, relatively advantaged people tend to remain advantaged whilst relatively disadvantaged people tend to remain disadvantaged. It is the relatively advantaged who benefit from opportunities for further upward mobility, so that inequalities and stratification tend to reproduce themselves (Seekings and Nattrass, 2005: 232-4, 277-80 and 322-6;Agüero et al, 2007;Woolard and Klasen, 2007;Girdwood and Leibbrandt, 2009;Ziervogel and Crankshaw, 2009;Finn and Leibbrandt, 2013). Our underclass thesis would be seriously undermined if it was shown that unemployed people in 'underclass' households were as likely to secure employment as unemployed people in more advantaged classes, that is, that social and cultural capital count for little.…”
Section: Class Differences Between the Lower Middle Working And Lowementioning
confidence: 99%
“…Our own and other work suggest that, over time, relatively advantaged people tend to remain advantaged whilst relatively disadvantaged people tend to remain disadvantaged. It is the relatively advantaged who benefit from opportunities for further upward mobility, so that inequalities and stratification tend to reproduce themselves (Seekings and Nattrass, 2005: 232-4, 277-80 and 322-6;Agüero et al, 2007;Woolard and Klasen, 2007;Girdwood and Leibbrandt, 2009;Ziervogel and Crankshaw, 2009;Finn and Leibbrandt, 2013). Our underclass thesis would be seriously undermined if it was shown that unemployed people in 'underclass' households were as likely to secure employment as unemployed people in more advantaged classes, that is, that social and cultural capital count for little.…”
Section: Class Differences Between the Lower Middle Working And Lowementioning
confidence: 99%
“…Our coding of occupations is based on the adaptation of the South African Standard Classification of Occupations (SASCO) suggested by Ziervogel and Crankshaw (). This coding convention, developed by Statistics South Africa, is based on the International Standard Classification of Occupation 1988 (ISCO‐88) of the International Labour Office (ILO).…”
Section: Data Descriptionmentioning
confidence: 99%
“…Due to the sparse nature of tertiary education qualifications in South Africa, this approach is likely to lead to artifactual biases in the estimates of transition probabilities between the four states. To deal with this problem, we follow Ziervogel and Crankshaw (2009) by reassigning the ISCO-88 major groups to four skills groups that more accurately reflect the distribution of skills in South Africa. Table 4 shows the effects of our recoding exercise in this regard.…”
Section: Occupational Statusmentioning
confidence: 99%